PELAKSANAAN QARDHUL HASAN DALAM PENDISTRIBUSIAN ZAKAT DI BAITUL QIRADH BAZNAS PROVINSI SUMATERA SELATAN MENURUT HUKUM EKONOMI SYARIAH - Gustina Martha (Tamwil, 2017)
This study aims to determine the legal review of the implementation of sharia economy qardhul hasan in the distribution of zakat in Baitul Qiradh BAZNAS South Sumatra Province. This study is a qualitative research using descriptive method of analysis, is to explain or describe the research data will be undertaken. This research was conducted in South Sumatra province BAZNAS by way of interviews and analysis of documents obtained investigators from data provided by BAZNAS South Sumatra Province. The results showed that the implementation of qardhul hasan in Baitul Qiradh BAZNAS South Sumatra province is not in accordance with the principles of muamalah because qardhul hasan funds derived from zakat funds were taken from the poor and routed through Baitul Qiradh using contract qardhul hasan to community groups indigent poor, and there is the addition of loan repayment in the form of donation of Rp. 5,000 each month specified in the contract qardhul hasan. To lend to others must meet in harmony and the terms of which the owner of the property was perfect while Zakat is not wholly owned pengelolah zakat (amil) so that the non-fulfillment of the pillars and the terms shahibul maal (owners of capital) and in qardhul hasan should not be any additional loan repayments with reference to the rules of fiqh "Every debt that is interesting benefit, then he riba".